Elevating English Proficiency: Crafting Esp-Based Digital Multimedia Learning Materials For Vocational Students In Indonesia - Musthafa Fadli Perkasyah; Erra Malinda; Annisa Faradilla; Apriliyanti Apriliyanti; Abdul Zebar; Tien Rafida (Departement of Mathematics Education, 2024)
The research aimed to create a systematic model for teaching ESP in vocational schools, using a qualitative approach combined with the Research and Development (R&D) method following Thiagarajan, Semmel, and Semme's 4Ds model. Preliminary research focused on defining student needs, leading to the development of ESP digital learning materials aligned with vocational skills. Data collected from two teachers and four classes, involving 115 students, included expert evaluations, observations, teacher assessments, interviews, and student questionnaires. The findings highlighted the successful implementation of tailored materials, positively impacting student engagement and teacher confidence despite identified resource and curriculum challenges. Overall, the study emphasized the significant role of these materials in enhancing both English proficiency and vocational skills in vocational high schools.